A Time-Domain Channel Estimation Method for MIMO-OFDM Systems with Low-Precision Quantization - Xiong, XingZhong; Wang, HaiFeng (Wireless personal communications, 2017)
Considering the cost and power consumption problems of the high-speed wireless communication receiver for high-precision quantization, this paper discusses the time-domain channel estimation for MIMO-OFDM systems with low-precision quantization. The low-precision quantization affects the performance of the system, however, by selecting the appropriate training sequence information, introducing the feedback dither control signal and using the optimized channel estimation algorithm, even with such low-precision (e.g., 1–3 bits) quantization, also can be obtained the performance of comparable the full precision MMSE criterion. Thereby reducing the complexity of the subsequent signal processing, cutting down the cost and power consumption, and effectively reducing the effect of low-precision quantization on the system performance. Theoretical analysis and simulation results show that this method has the characteristics of the fast convergence rate, higher estimation accuracy. Implement the receiver of the low cost, low power consumption and higher transmission efficiency of the system.